2002
DOI: 10.1017/s0021859602002034
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of lactating cows under grazing and indoor feeding conditions in the tropics

Abstract: The study reported examined the physiological changes between two groups of 6 Friesian-cross cows in mid-lactation; one group grazed outdoors without shade, the second group was housed indoors in an open-sided barn and fed cut-and-carry forage from the grazing area. All cows were machine-milked at 05.00 and 15.30 h daily. At 14.00 h dry bulb temperatures averaged 29·5 °C outdoors and 29·0 °C indoors whilst black globe temperatures were 36·2 and 29·5 °C respectively. Relative humidity averaged 76% outdoors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
2
1
3
Order By: Relevance
“…The observed high THI in summer agree with the findings by Gantner et al (2011), who found high values in summer and spring; thus, causing heat stress in animals (Prasanpanich et al 2002;Gantner et al 2011;Ganaie et al 2013). Generally, THI was lower than the values reported by Prasanpanich et al (2002), who monitored physiological responses of lactating cows in the tropics with means 79.5 and 78.3 for outdoor and indoor grazing animals, respectively.…”
Section: Light Coatssupporting
confidence: 89%
See 1 more Smart Citation
“…The observed high THI in summer agree with the findings by Gantner et al (2011), who found high values in summer and spring; thus, causing heat stress in animals (Prasanpanich et al 2002;Gantner et al 2011;Ganaie et al 2013). Generally, THI was lower than the values reported by Prasanpanich et al (2002), who monitored physiological responses of lactating cows in the tropics with means 79.5 and 78.3 for outdoor and indoor grazing animals, respectively.…”
Section: Light Coatssupporting
confidence: 89%
“…Generally, THI was lower than the values reported by Prasanpanich et al (2002), who monitored physiological responses of lactating cows in the tropics with means 79.5 and 78.3 for outdoor and indoor grazing animals, respectively. Similar findings by Aggarwal and Singh (2010) showed higher THI values in the hot-humid than in the hot-dry season causing heat stress in Murrah buffaloes.…”
Section: Light Coatscontrasting
confidence: 67%
“…Nevertheless, the levels were found to be within the range of reported values for cattle (2.5–4.2 mmol/l; Kaneko et al., 1997). This may indicate an adequate energy supply of animals (Rook and Line, 1961; Prasanpanich et al., 2002; Singh et al., 2002). It is, however, to consider that the role of glucose as a superior indicator for energy supply in the mature cattle is a matter of dispute, because it is regulated by an array of different factors (Mudron et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A alteração na FR, em função da facilidade de mensuração e da rápida resposta às alterações ambientais, tem sido proposta como um parâmetro fisiológico para a detecção do estresse no animal (BROWN-BRANDT et al, 2005;MADER et al, 2006;MARTELLO, 2006;MITLOEHNEN et al, 2001;PRASANPANICH et al, 2002;VALTORTA et al, 1997). Na presente pesquisa, das variáveis analisadas, foi a que apresentou melhor visibilidade dos efeitos dos diferentes tipos de sombreamento sobre os animais.…”
Section: Freqüência Respiratória (Fr)unclassified